The interplay between propelling efficiency, hydrodynamic position and energy cost of front crawl in 8 to 19-year-old swimmers - Zamparo, P.; Lazzer, S.; Antoniazzi, C.; Cedolin, S.; Avon, R.; Lesa, C. (European Journal of Applied Physiology, 2008)
The aim of this study was to investigate the interplay between the arm stroke efficiency (an index of propelling efficiency, "Eta" P) and the static and dynamic position in water (indexes of hydrodynamic resistance, W d) in determining the energy cost of front crawl (C) during a swimmer`s growth. These three parameters are indeed related by the following equation: C = Wd/(Eta P·Eta o) C=Wd(Po)where Eta o is the overall efficiency of swimming. The experiments were carried out on 72 swimmers (38 M and 34 F; 8-19 years) who were asked to swim at 1 m/s. The static position in water was assessed by measuring the underwater torque (T'); the dynamic position in water by measuring the projected frontal area (A eff). The ratio between the average values of the eldest to youngest class of age was 3.84 and 2.27 for T', 2.13 and 1.68 for A eff, and 1.13 and 1.24 for Eta P (in M and F, respectively). The increase in T' and in A eff was larger than the increase in efficiency suggesting that, in this age range, C should increase, the more so in M than F. Indeed, C increased by 1.58 in male and 1.17 in female swimmers. Based on the values of C and Eta P (and assuming a constant value of o) it is possible to estimate that, in this age range, W d increases by about 1.97 in male and 1.32 in female swimmers, an increase which is proportional to the observed increase in A eff.